2016
DOI: 10.1063/1.4944893
|View full text |Cite
|
Sign up to set email alerts
|

Robust acoustic wave manipulation of bubbly liquids

Abstract: Articles you may be interested inAn experimental study on resonance of oscillating air/vapor bubbles in water using a two-frequency acoustic apparatus Phys. Fluids 15, 1189 (2003); 10.1063/1.1561613 Viscous effects on the interaction force between two small gas bubbles in a weak acoustic field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…The experimental observations qualitatively agree with the present theory, where the front of the AIT wave was clearly indicated by a thin region of high bubble concentration. We also remark that despite a satisfactory agreement with experiments, computations using discrete weakly nonlinear collisionless models of bubbly liquids, 26,27 should be studied more systematically both from the theoretical and computational point of view.…”
Section: Polydisperse Systemsmentioning
confidence: 88%
See 2 more Smart Citations
“…The experimental observations qualitatively agree with the present theory, where the front of the AIT wave was clearly indicated by a thin region of high bubble concentration. We also remark that despite a satisfactory agreement with experiments, computations using discrete weakly nonlinear collisionless models of bubbly liquids, 26,27 should be studied more systematically both from the theoretical and computational point of view.…”
Section: Polydisperse Systemsmentioning
confidence: 88%
“…To bypass this difficulty, experiments were recently conducted to observe a water-air bubbly liquid exposed to an acoustic field of intensity below the cavitation threshold. [25][26][27] It was shown that bubbles can be "pushed" away from the acoustic source forming a region almost free from bubbles-the phenomenon termed as the acoustically induced transparency (AIT). It was also shown that the observed effect cannot be explained by well-known theories of single bubble drifting in an acoustic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…При самоор-ганизации множества пузырьков в ультразвуковом поле интенсивностью ниже кавитационного порога обнаруживается выталкивание пузырьков воздуха в воде от источника поля независимо от положе-ния пузырька в пространстве [3]. При этом возника-ет область, практически очищенная от пузырьков, в которой распределение поля давления постоянно меняется с движением фронта пузырьков, что фор-мирует двустороннее взаимодействие системы пу-зырьки-поле .…”
Section: Introductionunclassified
“…Для проведения экспериментальных исследований была разработана и собрана лабораторная установка (рис. 1) на базе длиннофокусного оптического микроскопа и высокоскоростной видеокамеры со скоростью записи изображений в 1000 fps [10]. Основной частью установки является проточная экспериментальная ячейка из прозрачного оргстекла с внутренними размерами 71 × 7 × 7 mm.…”
unclassified